Characteristics of General Language Teaching and Academic Language Teaching as a Foreign Language: Learner’s Views - Gökçen Göçen; İsmail Aydoğdu (Sakarya University Journal of Education)
Foreign language teaching is divided into general and special purpose language teaching. Foreign language education offers general language courses at five levels starting from A1 to C1. In addition to the four core language skills, grammar and vocabulary are also taught. Special-purpose language teaching is divided into two categories: professional and academic language. Academic language courses are also provided within a specific program and duration. This study compares general language teaching and academic language teaching based on learner views. Phenomenology, one of the qualitative research designs, was used in the study. In this context, the study data consists of the opinions of 64 learners in the Academic Turkish class at Sakarya University TÖMER. The learners were asked about the similarities and differences as well as the main features of these courses using a semi-structured interview form. The answers to the questions were analyzed by content analysis. This study identified 8 themes and 106 sub-themes. Although the themes occur at different frequencies in general language and academic language courses, the eight common themes are as follows: quality in teaching, purpose in teaching, subject in teaching, utilization of activities in teaching, language use in teaching, content in teaching, utilization of texts in teaching and process in teaching.